Disease-related knowledge in inflammatory bowel disease: experience of a tertiary care centre in a developing country in South Asia - Subasinghe, D; Wijekoon, N S; Nawarathne, N M M; Samarasekera, D N (Singapore Medical Association, 2010)
Introduction: Disease-related knowledge plays a critical role in facilitating patients' acceptance of their diagnosis and compliance with active participation in the treatment of inflammatory bowel disease (IBD). The aim of this study was to analyse the deficits in knowledge for future health education programmes. Methods: A validated questionnaire was used to assess and analyse disease-related knowledge among patients with ulcerative colitis (UC) and Crohn's disease who attended outpatient gastroenterology clinics of a tertiary care hospital in Sri Lanka. Results: There were 184 patients (83 males) with a mean age of 44.5 (range 20-78) years. 83.2 percent of the patients had UC. The mean duration of IBD was 8.17 (range 1-28) years, and 33.7 percent of the patients had IBD for over ten years. The mean Crohn's and Colitis Knowledge questionnaire score was 6.86. The majority (68.5 percent) of the patients were aware that sulfasalazine can be used to reduce exacerbations. There was no statistical difference in disease-related knowledge between genders, but the level of education showed a significant difference. Only 14.1 percent of patients were aware that prolonged IBD is a risk factor for colorectal cancer and that screening for colorectal cancer is important. 9.2 percent of the study population was aware of restorative proctocolectomy. Conclusion: There is a lack of knowledge regarding colorectal cancer risk and surgical interventions. There was no significant difference in the knowledge scores between genders but there was a significant association with the educational level.
Keywords: Crohn’s disease; disease-related knowledge; inflammatory bowel disease; ulcerative colitis